Kontribusi Kader Kesehatan Masyarakat Selama Masa Pandemi COVID-19 - Diksi Hera Berliana; Junaiti Sahar; Dwi Cahya Rahmadiyah (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine the involvement of cadres as partners of Puskesmas in overcoming the COVID-19 pandemic. The method used is a literature study through article searches in the PubMed, Scopus and Google Scholar databases. The results showed that four theme issues emerged, namely: (1) helping to promote health for COVID-19; (2) monitoring of health status of individuals and communities undergoing self-isolation; (3) strengthening the COVID-19 response through Community Based Surveillance (SBM); (4) maintain essential health services. In conclusion, the involvement of community health workers (CHWs) is one of the efforts that can help health workers to respond to the spread of the COVID-19 pandemic. Keywords: COVID-19, Public Health Cadre, Public Health Volunteer, Health Workers Volunteer